2022
DOI: 10.3390/ani12233431
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplementation with Vitamin A on Antioxidant and Intestinal Barrier Function of Broilers Co-Infected with Coccidia and Clostridium perfringens

Abstract: Necrotic enteritis (NE) impairs poultry production and causes great economic loss. The nutritional regulation of diets has the potential to alleviate NE. The present study was conducted to investigate the effects of dietary supplementation with vitamin A (VA) on the antioxidant and intestinal barrier function of broilers co-infected with coccidia and C. perfringens (CCP). In a 2 × 2 factorial arrangement, 336 one-day-old Ross 308 broilers were divided into four treatments with two levels of VA (0 or 12,000 IU/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
3
4
0
Order By: Relevance
“…The jejunal lesion score increased with NE challenge in the present study, indicating the successful establishment of NE. This was consistent with the decrease in feed intake and impairment of the intestinal barrier function in NE-challenged birds [ 27 ]. At the same time, serum glucose, total glyceride, calcium, phosphorus and uric acid levels were reduced with NE challenge as well.…”
Section: Discussionsupporting
confidence: 86%
“…The jejunal lesion score increased with NE challenge in the present study, indicating the successful establishment of NE. This was consistent with the decrease in feed intake and impairment of the intestinal barrier function in NE-challenged birds [ 27 ]. At the same time, serum glucose, total glyceride, calcium, phosphorus and uric acid levels were reduced with NE challenge as well.…”
Section: Discussionsupporting
confidence: 86%
“…When animals are exposed to pathogens, viruses, and harsh environments, the body produces large amounts of reactive oxygen species (ROS) and MDA, which may cause oxidative stress [ 24 ]. It has been shown that broilers with NE condition reduced antioxidant function, induced inflammatory response, and impaired intestinal barrier function [ 19 , 25 , 26 ]. Consistent with previous findings, we found that Jejunal H 2 O 2 and MDA contents were increased, and T-AOC, SOD, CAT, and GSH-Px levels were decreased by CCP challenge, which indicated that CCP co-infection caused oxidative stress in the broiler.…”
Section: Discussionmentioning
confidence: 99%
“…GSH-Px1 and GSH-Px3 belong to selenium-containing GSH-Px, which have the function of cleaning up reactive oxygen species, with the difference that GSH-Px1 exists in the cytoplasm and mitochondria, and GSH-Px3 exists in the extracellular [ 30 , 31 , 32 , 33 ]. Invasion by pathogens can upregulate the expression of the Nrf2 and keap1 genes, which causes oxidative stress in the organism and promotes the entry of Nrf2 into the nucleus to participate in the synthesis of several antioxidant enzymes in reaction to oxidative stress [ 19 , 34 , 35 ]. In our study, Keap1 and Nrf2 mRNA levels were elevated in the liver and jejunum, and jejunal GST and HO-1 mRNA levels were increased in the CCP-challenged broilers, suggesting that CCP infection induces oxidative stress in broilers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Dalloul et al (2002) [113] reported that vitamin A deficiency compromised the intestinal defense mechanism against E. acervulina infection, as evidenced by a reduced population of intraepithelial lymphocytes (CD4+ and CD8+ T cells) through alterations in concanavalin A-induced spleen lymphocyte proliferation. Moreover, vitamin A supplementation (12,000 IU/kg) enhanced intestinal morphometry and tight junction integrity in broiler chickens co-infected with Clostridium and Eimeria [119].…”
Section: Other Vitaminsmentioning
confidence: 99%